The Effect of Corporate Social Responsibility (CSR) on the Profitability of Bank Muamalat Indonesia Period 2013-2016 - Diah Khumairoh; Khodijah Anugrah Mahesa; Miya Darti (Yayasan Darussalam Bengkulu, 2023)
The purpose of this study was to determine the effect and how much influence the Corporate Social Responsibility (CSR) program has on Profitability. Where profitability is proxied into Return on Asset (ROA) and Return on Equity (ROE) in the annual report of Bank Muamalat Indonesia publication in 2013-2016. Researchers used a quantitative approach with simple regression data analysis techniques using the SPSS version 16 program. The results showed that Corporate Social Responsibility (CSR) had a significant effect on Return on Asset (ROA) with a sig value. (0.030) <0.05 and the coefficient of determination is 22.1%. Corporate Social Responsibility (CSR) has no significant effect on Return on Equity (ROE) with a sig value. (0.654) > 0.05 and the coefficient of determination is 12.0%.